Investment in renewable energy and emissions: Firm-level empirical evidence from the People's Republic of China - Dina Azhgaliyeva; Hai Le (Asian Development Bank Institute (ADBI), 2023)
This study investigates the impact of firms' emissions on their investments in renewable energy. Stricter environmental regulations are aimed at incentivizing firms to invest in low-emission/pollution technologies such as renewable energy. Recently, the People's Republic of China (PRC) announced a large number of environmental regulations in order to address emission and air pollution issues. Using the unique data set of annual firm-level data of 147 firms from the PRC that invested in renewable energy projects domestically during the period 2015-2020, our results demonstrate that firms with greater air pollution or greenhouse gas emissions (measured as a share of revenue) invest more in renewable energy (measured as a share of equity). The results have survived several robustness checks.
Keywords: Q53; Q58; Q42; G32; G38; 330; renewable energy; air pollution; People's Republic of China; GHG emissions; green investment; COVID-19